ASSAY METHOD DEVELOPMENT AND VALIDATION FOR SIMULTANEOUS QUANTITATIVE ESTIMATION OF DILOXANIDE FUROATE AND ORNIDAZOLE IN TABLETS BY RP-HPLC - Kumar, D. Vijay; Swetha, P.; Prasad, G. Sai; Kumar, A. Ashok (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: To develop an accurate, precise and linear Reverse Phase High Performance Liquid Chromatographic (RP-HPLC) method for simultaneous quantitative estimation of Diloxanide furoate and Ornidazole in tablets and validate as per ICH guidelines. Methods: The optimized method uses a reverse phase column, Waters Symmetry C18 (250 X 4.6 mm; 5Î¼), a mobile phase of tri ethyl ammonium phosphate buffer (pH 2.3):acetonitrile in the proportion of 40:60 v/v, flow rate of 1.0 ml/min and a detection wavelength of 270 nm using a UV detector. Results: The developed method resulted in Diloxanide furoate eluting at 4.31 min and Ornidazole at 2.64 min. Diloxanide furoate exhibited linearity in the range 46.87-140.62Î¼g/ml, while Ornidazole exhibited linearity in the range 31.25-93.75Î¼g/ml. The precision is exemplified by relative standard deviations of 1.02% for Diloxanide furoate and 0.514% for Ornidazole. Percentage Mean recoveries were found to be in the range of 98â€102, during accuracy studies. The limit of detection (LOD) for Diloxanide furoate and Ornidazole were found to be 122.54Âµg/ml and 81.54Âµg/ml respectively, while limit of quantitiation (LOQ) for Diloxanide furoate and Ornidazole were found to be 371.33Âµg/ml and 247.11Âµg/ml respectively. Conclusion: A simple, accurate, precise, linear and rapid RP-HPLC method was developed for simultaneous quantitative estimation of Diloxanide furoate and Ornidazole in tablets and validated as per ICH guidelines. Hence it can be used for the routine analysis of Diloxanide furoate and Ornidazole in tablets in various pharmaceutical industries. Â